Core outcome measures for exercise studies in people with multiple sclerosis: recommendations from a multidisciplinary consensus meeting. (October 2014) - Paul, Lorna; Coote, Susan; Crosbie, Jean; Dixon, Diane; Hale, Leigh; Holloway, Ed; McCrone, Paul; Miller, Linda; Saxton, John; Sincock, Caroline; White, Lesley
Evidence shows that exercise is beneficial for people with multiple sclerosis (MS); however, statistical pooling of data is difficult because of the diversity of outcome measures used. The objective of this review is to report the recommendations of an International Consensus Meeting for a core set of outcome measures for use in exercise studies in MS. From the 100 categories of the International Classification of Function Core Sets for MS, 57 categories were considered as likely/potentially likely to be affected by exercise and were clustered into seven core groups. Outcome measures to address each group were evaluated regarding, for example, psychometric properties. The following are recommended: Modified Fatigue Impact Scale (MFIS) or Fatigue Severity Scale (FSS) for energy and drive, 6-Minute Walk Test (6MWT) for exercise tolerance, Timed Up and Go (TUG) for muscle function and moving around, Multiple Sclerosis Impact Scale (MSIS-29) or Multiple Sclerosis Quality of Life-54 Instrument (MSQoL54) for quality of life and body mass index (BMI) or waist-hip ratio (WHR) for the health risks associated with excess body fat. A cost effectiveness analysis and qualitative evaluation should be included where possible. Using these core measures ensures that future meta-analyses of exercise studies in MS are more robust and thus more effectively inform practice.